2019
DOI: 10.1007/s42690-019-00056-z
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of host susceptibility, preference and offspring performance of Zeugodacus cucurbitae (Coquillett) (Diptera: Tephritidae) on different hosts

Abstract: The melon fruit fly, Zeugodacus cucurbitae (Coquillett) is a quarantine insect pest worldwide and affects the vegetable quality through its direct feeding and indirectly by passing way for secondary pathogens. This study investigated the host susceptibility, preference and offspring performance of Z. cucurbitae under the laboratory conditions. Different vegetable hosts i.e., brinjal (Solanum melongena L.), bitter gourd (Momordica charantia L.), zucchini (Cucurbita pepo L.), bottle gourd (Lagenaria siceraria [M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Differences in the species and cultivars of Solanaceae crops had a significant impact on the aspect of induced oviposition and trapping of gravid Z. tau females. This is consistent with previous research on several polyphagous fruit flies (Diptera: Tephritidae), such as B. zonata [51,52], Z. cucurbitae [52,53], A. obliqua [54], Neoceratitis cyanescens [55], B. oleae [56], B. tryoni [57,58], B. dorsalis [23,40,59,60], and B. latifrons [61,62]; these studies found that the ability to attract fruit flies differed between species and cultivars of host plants. Polyphagous fruit flies with higher olfactory plasticity are able to recognize and use more hosts and choose their preferred host plants more than [63].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Differences in the species and cultivars of Solanaceae crops had a significant impact on the aspect of induced oviposition and trapping of gravid Z. tau females. This is consistent with previous research on several polyphagous fruit flies (Diptera: Tephritidae), such as B. zonata [51,52], Z. cucurbitae [52,53], A. obliqua [54], Neoceratitis cyanescens [55], B. oleae [56], B. tryoni [57,58], B. dorsalis [23,40,59,60], and B. latifrons [61,62]; these studies found that the ability to attract fruit flies differed between species and cultivars of host plants. Polyphagous fruit flies with higher olfactory plasticity are able to recognize and use more hosts and choose their preferred host plants more than [63].…”
Section: Discussionsupporting
confidence: 92%
“…Polyphagous fruit flies with higher olfactory plasticity are able to recognize and use more hosts and choose their preferred host plants more than [63]. The previous studies indicated that hosts with greater attraction were advantageous to the offspring performance of fruit flies [51,53,[56][57][58]60]. The previous studies verified a positive correlation between the attractiveness of Cucurbitaceae, Myrtaceae, and Rutaceae crops to Z. tau and the offspring performance (larval survival, pupation rate, and emergence rate) of Z. tau [64].…”
Section: Discussionmentioning
confidence: 87%
“…A significant influence of host plants was observed on the different developmental parameters of Zeugodacus cucurbitae (Coquillett) [37]. Our results suggested that the fruit host may change ovipositional behaviours, either increasing or decreasing the sizes of the egg masses.…”
Section: Discussionmentioning
confidence: 61%
“…Among them, the melon fly Zeugodacus cucurbitae (Coquillett; Diptera: Tephritidae) is polyphagous and one of the most destructive species, severely affecting the production of cucurbits (De Meyer et al, 2015; Mwatawala et al, 2009). This pest has a high dispersal potential and reproduction rate (Farooq et al, 2020; Mwatawala et al, 2009). Females lay their eggs under the skin of the fruit, allowing the hatchlings to feed inside and causing the fruit to rot (Stonehouse et al, 2007).…”
Section: Introductionmentioning
confidence: 99%